A multisite and anti-cross-contamination brief touch sampler for asteroid sample return mission☆. (December 2022) - Li, Junlin; Zhou, Weijia; Zhang, Wei; Li, Zhenxin; Zhang, Wei; Cheng, Qinkun; Huang, Hao; Zhang, Shengyong
Abstract: Asteroids are the "time capsules" of the solar system, storing the origin and evolution of the protoplanetary disk. In addition, they are the remaining "building blocks" of the Earth and terrestrial planets, preserving the initial materials of the latter. To study the first 10 million years history of the solar system, a multisite and anti-cross-contamination brief touch sampler (BTS) was designed for the asteroid sample return (ASR) mission of the Chinese Academy of Sciences (CAS). The sampler provides a pair of counterrotating brush wheels to balance the angular momentum during the sampling processes. A combination of brushes with different shapes and stiffnesses are used to maximize the success of the sample acquisition and guide the sample into the sample canister through the anti-impact guide cover. The sample canister is designed with three sample storage containers with independently sealed doors. The canister can accommodate samples from three different sites without cross contamination to conveniently study the substance distribution of asteroids. Because asteroids have typical microgravity characteristics, prototype verification in a simulated microgravity environment was also conducted. The experimental results show that the sample acquisition processes are effective and that a minimum of 2 g of simulated regolith particles can be sampled within 3 s. Highlights: The profile of the Chinese Academy of Sciences first ASR mission introdudced. The design of the sampling apparatus BTS is discussed in detail. Manipulator and drop tower microgravity device are introdudced. Preliminary microgravity results are presented. Some conclusion remarks are made.